The Aegean Dispute - Constantinides, Stephanos; Arnopoulos, Paris (Études helléniques / Hellenic Studies, 1996)
1996 will be remembered as the year of rhe "Aegean Crisis". The old dispute reopened in January with the lmia crisis. It flared up in May wirh Turkey's diplomatic claim on the island of Gavdos, reheated in August with its military academy's allegation of sovereignty over a hundred islets and islands in the Aegean as far as Crete, and continued unabated throughout the fall, punctuated by Turkish airforce flights over the archipelago. The Aegean confrontarion revolves around three major points of contention: territorial waters, continental shelf, and air space. The origin of this dispute dates from 1973, when Turkey raised the question of delimination of the continental shelf. The coup d'état organized by the Greek junta against Cypriot president Makarios the following year gave Turkey the opportunity ro invade Cyprus. Since then, Greco-Turkish relations have deteriorated from bad to worse and the Aegean issue has flared up periodically, threatening to explode into war.